Volumetric arterial wall shear stress calculation based on cine phase contrast MRI. Issue 2 (17th January 2014) - Potters, Wouter V.; van Ooij, Pim; Marquering, Henk; vanBavel, Ed; Nederveen, Aart J.
<x xml:space="preserve">Abstract</x> Purpose To assess the accuracy and precision of a volumetric wall shear stress (WSS) calculation method applied to cine phase contrast magnetic resonance imaging (PC‐MRI) data. Materials and Methods Volumetric WSS vectors were calculated in software phantoms. WSS algorithm parameters were optimized and the influence of spatial resolution and segmentation was evaluated. Subsequently, 2D cine PC‐MRI data in the carotid and the aorta at varying spatial resolutions were obtained (n = 2) and compared with the simulations. Finally, volumetric WSS was calculated in 3D cine PC‐MRI data of the carotid bifurcation and the aorta (n = 6). Results We found that at least 8 voxels across the diameter are required to obtain a WSS accuracy of 5% and a precision of 20% in software phantoms. Systematic WSS quantification errors up to 40% were found in the case of segmentation errors. The in vivo measurements using 2D cine PC‐MRI exhibited WSS increase at increasing spatial resolutions, similar to the results in software phantoms. Volumetric WSS vectors were successfully calculated in three healthy carotid bifurcations and aortas. Conclusion The effects of resolution and segmentation on the accuracy and precision of the WSS algorithm were quantified. We were able to calculate volumetric WSS in the carotid bifurcation and the aorta. J. Magn. Reson. Imaging 2015;41:505–516.© 2013 Wiley Periodicals, Inc.